Does using anatomical models improve patient satisfaction in orthopaedic consenting? Single-blinded randomised controlled trial. Issue 3 (June 2019) - Sugand, K.; Malik, H.H.; Newman, S.; Spicer, D.; Reilly, P.; Gupte, C.M.
Abstract: Background: Patient satisfaction in consenting is a major pillar of clinical governance and healthcare quality assessment. The purpose was to observe the effect of using 3D anatomical models of knee and shoulder joints on patient satisfaction during informed consent in the largest single-blinded randomised controlled trial in this field. Methods: 52 patients undergoing elective knee or shoulder surgery were randomised into two groups when being consented. The intervention group (n = 26) was shown an anatomical model of the knee/shoulder joint while the control group (n = 26) was given only a verbal explanation without a model. Patients rated their satisfaction on the validated Medical Interview Satisfaction Scale (MISS-26) questionnaire. Semi-structured interviews were analysed for specific themes to determine key factors that influenced patient satisfaction. The mean score ±SD were calculated with significance set at p < 0.05. Results: There was a significant difference in the overall satisfaction between the control and intervention cohorts (MISS-26 score 4.33 [86.6%] ± 0.646 vs 4.70 [94.0%] ± 0.335 respectively, 7.4% improvement, 8.5% difference, p = 0.01). Behavioural criteria showed a 13% increase in satisfaction (p = 0.02). Semi-structured interviews determined that the factors influencing satisfaction included the surgeon's interpersonal manner, the use of the visual aid and seeing the consultant surgeon in clinic. All patients in the intervention cohort identified factors contributing to their satisfaction, whereas a fifth of the control cohort claimed nothing at all made them feel satisfied. Conclusion: Anatomical models as visual aids significantly increased patient satisfaction during the consenting process and played an integral part of the surgeon's explanation. Patients exposed to anatomical models also claimed to be more satisfied with the surgeon's inter-personal skills. This study recommends the use of anatomical models, which are both cost-effective and easily implementable, during explanation and consent for orthopaedic procedures.